Assessment of shoulder active range of motion in prone versus supine: a reliability and concurrent validity study. (3rd October 2015) - Furness, James; Johnstone, Scott; Hing, Wayne; Abbott, Allan; Climstein, Mike
Abstract: Background : As swimming and surfing are prone dominant sports, it would be more sport specific to assess shoulder active range of motion in this position. Objectives : To determine the reliability of the inclinometer and HALO© for assessing shoulder active range of motion in supine and prone and the concurrent validity of the HALO©. Concurrent validity is based on the comparison of the HALO© and inclinometer. To determine if active range of motion (AROM) differences exists between prone and supine when assessing shoulder internal (IR) and external rotation (ER). Design : The design included clinical measurement, reliability and validity. Methods : Thirty shoulders (mean age = 26.8 years) without pathology were evaluated. Measurements were taken in supine and prone with both an inclinometer and HALO© device. Results : Active ER ROM in prone was significantly higher than in supine when using both devices. Intra-rater reliability (within and between session) intraclass correlation coefficient (ICC) values ranged between 0.82–0.99 for both devices in supine and prone. An ICC test revealed a significant ( p  < 0.01) correlation for both devices in IR and ER movements (ICC3, 1  = 0.87 and ICC3, 1  = 0.72), respectively. Conclusion : This study has shown prone assessment of active ER and IR ROM to be a reliable and appropriate method for prone dominant athletes (swimmers and surfers). In this study greater ER ROM was achieved in prone compared to supine. This finding highlights the importance of standardizing the test position for initial and follow up assessments. Furthermore the HALO© and inclinometer have been shown to be reliable tools that show good concurrent validity.